Gestión del cambio y compromiso en los colaboradores de la Municipalidad Provincial de Maynas,2020 - Pérez Alvarez, Darwin Andrés (2022)
his study aimed to examine the relationship between change management and employee commitment at the Provincial Municipality of Maynas in 2020. Using a basic research approach with a correlational level and non-experimental design, researchers sampled 185 individuals from a workforce of 372 employees. Data collection was conducted through surveys using questionnaires. The findings revealed a significant relationship between change management and overall employee commitment, supported by a statistical significance of 0.000 and a high positive correlation coefficient of 0.850. Further analysis demonstrated significant relationships between change management and specific dimensions of commitment: With affective commitment: significance of 0.000 and a high positive correlation of 0.858.With continuity commitment: significance of 0.000 and a high positive correlation of 0.850. With normative commitment: significance of 0.000 and a high positive correlation of 0.856 These results consistently show that change management practices have strong positive associations with all measured aspects of employee commitment within this municipal organization.